Complementary methods for the prevention and treatment of stress-induced mastopathy - Chukhraev, N.; Zukow, W.; Vladimirova, N.; Chukhraeva, E.; Tereshchenko, O. (Journal of Education, Health and Sport, 2022)
The article considers the relationship between stress and diseases of the female reproductive system. A method for the rehabilitation of patients with mastopathy resulting from psycho-emotional stress (stress) based on the use of complementary methods of prevention and medical rehabilitation is proposed.